Pth4, an ancient parathyroid hormone lost in eutherian mammals, reveals a new brain‐to‐bone signaling pathway. Issue 2 (24th October 2016) - Suarez‐Bregua, Paula; Torres‐Nuñez, Eva; Saxena, Ankur; Guerreiro, Pedro; Braasch, Ingo; Prober, David A.; Moran, Paloma; Cerda‐Reverter, Jose Miguel; Du, Shao Jun; Adrio, Fatima; Power, Deborah M.; Canario, Adelino V. M.; et al.
ABSTRACT: Regulation of bone development, growth, and remodeling traditionally has been thought to depend on endocrine and autocrine/paracrine modulators. Recently, however, brain‐derived signals have emerged as key regulators of bone metabolism, although their mechanisms of action have been poorly understood. We reveal the existence of an ancient parathyroid hormone (Pth)4 in zebrafish that was secondarily lost in the eutherian mammals' lineage, including humans, and that is specifically expressed in neurons of the hypothalamus and appears to be a central neural regulator of bone development and mineral homeostasis. Transgenic fish lines enabled mapping of axonal projections leading from the hypothalamus to the brainstem and spinal cord. Targeted laser ablation demonstrated an essential role for of pth4 ‐expressing neurons in larval bone mineralization. Moreover, we show that Runx2 is a direct regulator of pth4 expression and that Pth4 can activate cAMP signaling mediated by Pth receptors. Finally, gain‐of‐function experiments show that Pth4 can alter calcium/phosphorus levels and affect expression of genes involved in phosphate homeostasis. Based on our discovery and characterization of Pth4, we propose a model for evolution of bone homeostasis in the context of the vertebrate transition from an aquatic to a terrestrial lifestyle.—Suarez‐Bregua, P., Torres‐Nuñez, E., Saxena, A., Guerreiro, P., Braasch, I., Prober, D.A., Moran, P., Cerda‐Reverter, J. M., Du, S. J., Adrio, F., Power, D. M., Canario, A. V. M., Postlethwait, J. H., Bronner, M E., Cañestro, C., Rotllant, J. Pth4, an ancient parathyroid hormone lost in eutherian mammals, reveals a new brain‐to‐bone signaling pathway. FASEB J. 31, 569–583 (2017). http://www.fasebj.org